2016
DOI: 10.1016/j.jtbi.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

An in silico model to demonstrate the effects of Maspin on cancer cell dynamics

Abstract: Most cancer treatments efficacy depends on tumor metastasis suppression, where tumor suppressor genes play an important role. Maspin (Mammary Serine Protease Inhibitor), an non-inhibitory serpin has been reported as a potential tumor suppressor to influence cell migration, adhesion, proliferation and apoptosis in in vitro and in vivo experiments in last two decades. Lack of computational investigations hinders its ability to go through clinical trials. Previously, we reported first computational model for masp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
(111 reference statements)
1
8
0
Order By: Relevance
“…Also, cells transfected with wild type maspin showed a slight increase in the content of both G-actin and F-actin which corresponds with its phenotype of a thick actin periphery and large flattened phenotype. It supports the finding that MCF7 cells stably expressing wild type maspin significantly increased cell adhesion by 113±5% on a laminin matrix and by 4576% on either collagen I or fibronectin matrices, in comparison to cells expressing vector only (Al-Mamun et al, 2016a). Also, GLCM values from our current analysis, we saw that ruffling regions of control cells (without maspin) are polarized and elongated as their entropy value is lower.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Also, cells transfected with wild type maspin showed a slight increase in the content of both G-actin and F-actin which corresponds with its phenotype of a thick actin periphery and large flattened phenotype. It supports the finding that MCF7 cells stably expressing wild type maspin significantly increased cell adhesion by 113±5% on a laminin matrix and by 4576% on either collagen I or fibronectin matrices, in comparison to cells expressing vector only (Al-Mamun et al, 2016a). Also, GLCM values from our current analysis, we saw that ruffling regions of control cells (without maspin) are polarized and elongated as their entropy value is lower.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported previously that maspin triggers several cellular processes which get reflected on cell behavior and cytoskeletal architecture (Odero-Marah et al, 2003;Qin & Zhang, 2010;Lara et al, 2012;Al-Mamun et al, 2016a). In a recent attempt, Al-Mamun et al, (2016b) showed that an image processing tool can be used to quantify three cellular parts: nuclei, cytoplasm and ruffling regions to observe the changes in shape and behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further demonstrated that incubation of SAS and OECM-1 cells with iron chelators enhanced the expressions of NDRG3 dose-dependently ( Figure 2 and Figure 3 ). Maspin is a non-inhibitory serpin and has been reported as a potential tumor suppressor gene in several cancers including OSCC [ 24 , 25 , 26 , 27 , 37 , 38 ]. Our results indicate that Dp44mT treatment enhanced Maspin expressions in SAS and OECM-1 cells; however, DFO increased Maspin expressions only in SAS cells, and deferasirox treatment did not affect Maspin expressions in both OSCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…SERPINB5 was reported to be a tumor suppressor by inducing apoptosis and inhibiting proliferation, invasion, and migration of tumor cells [19, 20]. No studies had examined associations of SERPINB5 rs17071138 T/C , rs3744941 C/T , and rs8089104 T/C genetic polymorphisms with susceptibility to oral cancer.…”
Section: Discussionmentioning
confidence: 99%